Discourse of the Relationship Between Dakwah and Politics in the Framework of Contemporary Study - Hasibuan, Susanti (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
Contemporary da'wah is not only interpreted as the transformation of Islamic values through lectures between da'i and mad'u, more than that, da'wah must be a driver and motivator in a modernization movement as an antidote to negative access through political access. This study uses a literature review method by exploring various literature that examines da'wah studies, data obtained from books, journal articles, theses and papers. Data analysis is carried out by synthesizing information from various sources to form a comprehensive picture of the research topic. The results of the study show that da'wah must absorb various dimensions of life and all aspects related to society, including political activities. In the process, da'wah views that Islam cannot be separated from politics and is also a very complete religion in regulating all human life, including religion and state affairs. This is the joint of totality in Islam which in the practice of life must be applied. There is a moral responsibility carried by Islam when it appears as a religion that perfects previous religions. In addition, da'wah is a reconstruction of society by including values that are in accordance with Islamic teachings.